Özel bir üniversitedeki öğrencilerin cinsel yolla bulaşan enfeksiyonlar hakkındaki bilgi düzeylerinin incelenmesi - Çetin, Canan (İstanbul Medipol Üniversitesi Sağlık Bilimleri Enstitüsü, 2015)
Amaç: Araştırma, İstanbul Medipol Üniversitesi Sağlık Bilimleri Fakültesi 4. sınıf öğrencilerinin cinsel yolla bulaşan enfeksiyonlar hakkındaki bilgi düzeylerinin incelenmesi amacıyla tanımlayıcı olarak yapıldı. Materyal ve Metod: Araştırma evrenini 2014-2015 eğitim-öğretim yılı güz döneminde İstanbul Medipol Üniversitesi Sağlık Bilimleri Fakültesi'nde hemşirelik, beslenme ve diyetetik, fizik tedavi ve rehabilitasyon ve sağlık yönetimi bölümlerinin son sınıfına kayıt yaptıran toplam 296 öğrenci oluşturdu. Anket sürecinin sonunda toplam 148 öğrenciye ulaşılarak kullanılabilir anket elde edildi. Veriler, gerekli izinler alındıktan sonra anket uygulama yöntemiyle toplandı. İstatistiksel değerlendirmede Kolmogorov – Smirnov, Pearson Ki-Kare, Kruskal Wallis testleri kullanıldı. Bulgular: Öğrencilerin yaş ortalaması 22 ± 1,5 olup %80,4'ünü kız öğrenciler, %19,6'sını erkek öğrenciler oluşturdu. Öğrencilerin büyük çoğunluğu cinsel konuları aileleriyle konuşamadıklarını ifade etti. Cinsel sağlık bilgilerini en çok okuldan ve en az aileden öğrendiklerini belirttiler. Öğrencilerin tercih ettikleri korunma yönetimine göre bilgi düzeyleri arasında anlamlı ilişki bulundu (p<0,05). Bölümler arasında ders içeriğinde cinsel sağlık eğitimi alan ve almayan öğrencilerin bilgi düzeyleri arasında anlamlı fark bulunmadı (p>0,05). Öğrencilerin cinsel konularla ilgili bilgileri iyi olmasına karşın bu konuda eğitim almak istediklerini belirttiler. Sonuç: Araştırma bulgularına göre üniversite öğrencilerinin cinsel yolla bulaşan enfeksiyonlar konusundaki bilgilerinin yeterli olduğuna fakat bu konuda riskli davranışlar sergileyebilecekleri sonucuna varıldı.

Objective: The purpose of the study was to determine the knowledge level of Medipol Istanbul University Faculty of Health Sciences 4th class students about sexually transmitted infections as descriptive. Material Method: Research universe was formed by Istanbul Medipol University fall semester of the 2014-2015 academic year; Faculty of Health Sciences Nursing, Nutrition and Dietetics, Physiotherapy and Rehabilitation, and has a total of 296 students enrolled in the final year of the Health Management section. At the end of the survey period, reaching a total of 148 usable responses were obtained. Data were collected through survey method after obtaining the necessary permits. Kolmogorov - Smirnov, Pearson chi-square, Kruskal-Wallis tests was used for statistical evaluation. Results: The average age of students was 22 ± 1,5 to %80,4 female students constitute %19,6 of male students. the vast majority of students expressed that, they are not doing any sexual issues conversation with their families. Students indicated that, most of the Sexual health information learned from school; (but) however, they learned least from their family. According to their preferred contraceptive methods was a significant relationship between students' knowledge (p < 0,05). According to their preferred contraceptive methods was a significant relationship between students' knowledge (p < 0,05). Sections of the course content of sexual health education were no significant difference between students with and without the knowledge level (p> 0,05). Despite of good knowledge of regarding sexual matters, students indicate that they wanted to get education to increase their knowledge in this regard. Conclusion: According to the findings, students have sufficient knowledge on sexually transmitted infections. But, they may behave risky in this manner.
Investigation of students knowledge level about sexually transmitted infections at one of the private university
Keywords: Bilgi; Cinsel Yolla Bulaşan Enfeksiyonlar; Öğrenci; Üniversite; Knowledge; Sexually Transmitted Infections; Student; University